Hearing the Silent Voices: Narratives of Health Care and Homelessness. (1st May 2013) - Wise, Caitlin; Phillips, Kenneth
<x xml:space="preserve">Abstract</x> Most homeless individuals lack adequate health care. With existing literature as a backdrop, this study sought to understand the experience of homeless persons in the health care system. Using a phenomenological approach, 11 homeless participants were interviewed and the transcripts from these interviews were analyzed for meaning. The health care experiences of the participants could be understood only when viewed within the context of homelessness. The four polar themes that emerged from the analysis—same/different, fair/unfair, freedom/barriers, and choice/no choice—highlighted the great divide between the health care experiences of those with a home and those without. Such understanding can help mental health nurses provide more appropriate care to this population.